2022
DOI: 10.1519/jsc.0000000000004263
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Static Stretching and Foam Rolling With or Without Vibration on the Range of Motion, Muscle Performance, and Tissue Hardness of the Knee Extensor

Abstract: Nakamura, M, Konrad, A, Kasahara, K, Yoshida, R, Murakami, Y, Sato, S, Aizawa, K, Koizumi, R, and Wilke, J. The combined effect of static stretching and foam rolling with or without vibration on the range of motion, muscle performance, and tissue hardness of the knee extensor. J Strength Cond Res 37(2): 322–327, 2023—Although the combination of static stretching (SS) and foam rolling (FR) is frequently used for warm-up in sports, the effect of the intervention order is unclear. This study compared mechanical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Therefore, an SS intervention should be avoided in sports requiring explosive muscle strength and balance function. On the other hand, it has been reported that a dynamic warm-up ( Samson, et al, 2012 ; Reid, JC et al, 2018 ), aerobic exercise ( Takeuchi and Nakamura, 2020 ; Takeuchi et al, 2021b ), or foam rolling with and without vibration ( Nakamura et al, 2022 ) after an SS intervention has a potentiation effect for the stretch-induced force deficit. Thus, it will be necessary to establish an optimal warm-up routine by investigating the effects of an SS intervention in actual warm-up routines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an SS intervention should be avoided in sports requiring explosive muscle strength and balance function. On the other hand, it has been reported that a dynamic warm-up ( Samson, et al, 2012 ; Reid, JC et al, 2018 ), aerobic exercise ( Takeuchi and Nakamura, 2020 ; Takeuchi et al, 2021b ), or foam rolling with and without vibration ( Nakamura et al, 2022 ) after an SS intervention has a potentiation effect for the stretch-induced force deficit. Thus, it will be necessary to establish an optimal warm-up routine by investigating the effects of an SS intervention in actual warm-up routines.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a history of neuromuscular disease and musculoskeletal injury involving the lower extremities were excluded. The required sample size for a repeated-measures two-way analysis of variance (ANOVA) (effect size = 0.25 [large when considering interaction effects for 2-way ANOVAs], α error = 0.05, and power = 0.95) based on our previous study’s ROM results [ 21 ] using G* power 3.1 software (Heinrich Heine University, Dusseldorf, Germany) was more than 9 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with a history of neuromuscular disease and musculoskeletal injury involving the lower extremities were excluded. The required sample size for a repeated-measures two-way analysis of variance (ANOVA) (effect size = 0.25 [large when considering interaction effects for 2-way ANOVAs], αerror = 0.05, and power = 0.80) based on our previous study’s ROM results [ 14 ] using G* power 3.1 software (Heinrich Heine University, Dusseldorf, Germany) was more than eight participants.…”
Section: Methodsmentioning
confidence: 99%